Generation Z and novel plant-based food alternatives - Bogueva, Diana; Marinova, Dora (Elsevier, 2023)
Creating novel options and using new technologies can enhance the quality, safety, productivity, sustainability and nutritional value of food while securing a better supply. Developed to form part of the sustainability transition, the future of the novel plant-sourced food alternatives is influenced by consumer acceptance or rejection. Representing 30% of the world’s population, understanding Generation Z’s (Gen Z’s) consumer viewpoints is important in this respect.